HUBUNGAN KARAKTERISTIK SOSIAL EKONOMI RUMAH TANGGA DENGAN PEMENUHAN HAK ANAK DI WILAYAH DAMPINGAN PLAN INTERNATIONAL INDONESIA PROGRAM UNIT SIKKA, NUSA TENGGARA TIMUR - Hastuti, Dwi; Sebho, Kasianus; Lamawuran, Yosef Lega (Jurnal Ilmu Keluarga dan Konsumen, 2010)
The study was conducted at PLAN’s area in District of Sikka, East Nusa Tenggara Province. There were five villages at Sub-district of Magepanda selected as location of the study which were Desa Magepanda, Desa Kolisia B, Desa Kolisia, Desa Done, dan Desa Reroroja. All households with children ages 0-18 years in those villages were chosen as samples of the study for a total of 2626 households. This report analyzes using a secondary data collected by Plan International Indonesia PU Sikka. Based on secondary data, then a descriptive statistics using frequency distribution was applied, while inferential statistics were applied using t-student analysis and Spearman rank correlation analysis. Results showed that more than half of samples (53%) were classified low in term of socio economic status. The study found that 75,6% of children have no birth certificate; 58,4% have no involvement at all on civil voices regarding child’s issue at village level; and only 36,7% of children living at home with flush toilet. In term of health it was found that more than 55 percent of children received medication, immunization and exlussive breast feeding, which describe an adequate health access and practices. With regard to child’s right for leissure activities, it showed that only 29,4% of under five years old children played and supervised, the rest played alone and unsupervised. In educational needs results showed that only 10% of children attended to early childhood education program (PAUD), and among 7-18 years old children in the sample there was 16,7% have no education, and those children attended to high school only 10%. However more than half of the households (51,4%) considered as moderate for their child’s right fulfillement. Statistical analysis showed differences among villages in fulfilling to child’s right. Meanwhile there were significant and possitive relationship between socio economic status and child right’s fulfillment, which means that the better the socio economic status of the family is the better the child’s right fulfillment.